2021
DOI: 10.1371/journal.pone.0253407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antigen- and RT-PCR-based testing strategies for detection of SARS-CoV-2 in two high-exposure settings

Abstract: Surveillance testing for infectious disease is an important tool to combat disease transmission at the population level. During the SARS-CoV-2 pandemic, RT-PCR tests have been considered the gold standard due to their high sensitivity and specificity. However, RT-PCR tests for SARS-CoV-2 have been shown to return positive results when performed to individuals who are past the infectious stage of the disease. Meanwhile, antigen-based tests are often treated as a less accurate substitute for RT-PCR, however, new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…One of the advantages of using saliva is that repeated surveillance testing of non-symptomatic individuals is possible; it can be difficult for patients to tolerate repeated nasopharyngeal swabs. Frequency tolerability is an often-cited advantage of antigen-based testing over RT-PCR for surveillance, along with cost of the test ( 4 , 27 ). Our saliva test is also low-cost ($4-6 per test including labor and reagents) as it does not require specialized collection devices or extraction reagents ( 13 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of using saliva is that repeated surveillance testing of non-symptomatic individuals is possible; it can be difficult for patients to tolerate repeated nasopharyngeal swabs. Frequency tolerability is an often-cited advantage of antigen-based testing over RT-PCR for surveillance, along with cost of the test ( 4 , 27 ). Our saliva test is also low-cost ($4-6 per test including labor and reagents) as it does not require specialized collection devices or extraction reagents ( 13 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because a large population of infected, contagious individuals are asymptomatic or pre-symptomatic, readily accessible testing is essential to identify and isolate these individuals ( 2 ). Testing frequency and turnaround time are critical components to reducing outbreaks regardless of testing method ( 3 , 4 ); however, supply chain shortages early on in the pandemic limited widespread testing ( 5 , 6 ). Testing capacity was also exacerbated in rural areas with less access to testing centers and clinical laboratories ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…RATs represent an efficient and cost-effective means for SARS-CoV-2 testing in both symptomatic and asymptomatic screening populations. Love et al recently demonstrated that frequency of testing, regardless of whether RT-PCR or rapid antigen testing is employed, in combination with effective quarantine, can provide an effective strategy to suppress the spread of SARS-CoV-2 ( 12 ). In real-world settings, the need for quarantine could be identified sooner following performance of a RAT, compared to a RT-PCR test, with a reflex RT-PCR test used to confirm the RAT result.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dedicated infrastructure and technical expertise are not required for RATs during point-of-care testing ( 10 ). Further, RATs have a better predictive value for infectiousness compared to RT-PCR ( 11 ), and recent epidemiological modeling shows that RAT-based surveillance testing, in combination with sequestration, can effectively reduce both disease burden and economic cost associated with the management of COVID-19 ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing antigenic and molecular testing regimes to control COVID-19 report that mass antigen testing alone is an acceptable alternative to strategies that include molecular testing 8,9,10 . In agreement, we found that mass antigen testing at a sufficient sensitivity can detect and isolate almost all individuals infected with a concordant variant.…”
Section: Discussionmentioning
confidence: 99%